Carcass characteristics and tissue composition of the meat of feedlot lambs fed high-grain diets - Guilherme Meneghello Carvalho Bernardes (Semina: Ciências Agrárias, 2018)
This study aimed to evaluate the effect of using different high-grain diets on the carcass characteristics and tissue composition of the meat of feedlot-finished lambs. Thirty-two male castrated Texel lambs born from single births and weaned at approximately 50 days of age were allotted to treatments that consisted of different unprocessed grains, as follows: corn grain, white oat grain, black oat grain, or grain of rice in the husk. The animals were slaughtered upon reaching the pre-established slaughter weight of 32 kg, which corresponds to 60% of the mature weight of their mothers. Lambs fed the high-corn grain diet had higher weights and yields of hot and cold carcass and larger loin-eye areas than those finished in the feedlot receiving high-grain diets based on white oat, black oat, or rice in the husk. Additionally, they had a higher degree of fatness and a thicker subcutaneous fat layer at slaughter, which lead to decreased cooler shrink loss. The neck, shoulder, ribs, and leg cuts were heavier in lambs fed the high-corn grain diet. By contrast, these lambs had a lower proportion of leg, more rib, and higher meat fat content, which may be undesirable for the consumer market. The use of high-corn grain diets, in comparison with high-grain diets based on black oat, white oat, and rice in the husk, may be recommended for finishing lambs in the feedlot when they are slaughtered at similar weights.